Factors affecting the Customers’ Decision to Use Self-Service Laundry at Wash Xpress in Bangkok (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the factors influencing customers’ decisions to use self-service laundry services at Wash Xpress in Bangkok. This quantitative study employs a convenience sampling method, collecting data from 385 customers through questionnaires. The data were analyzed using percentage, mean, standard deviation, t-test, one-way ANOVA, factor analysis, and multiple regression analysis. The results indicate that most respondents were female, aged 26-35 years, single, with an education level below a bachelor’s degree, employed in private companies, and earning an average monthly income of less than 15,000 THB. The inferential statistical analysis found that personal factors, specifically age and occupation, significantly influenced the decision to use self-service laundry services at a statistical significance level of 0.05. Additionally, the marketing mix factors of environment, process, and personnel significantly influenced the decision to use self-service laundry services at a statistical significance level of 0.05. The estimation model explains 48.4% of the variance in customers’ decisions to use Wash Xpress self-service laundry services in Bangkok.